High-performance release film for MLCC and method for manufacturing the same

CN122898013APending Publication Date: 2026-10-13AI BOTE (HUIZHOU) NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611317692.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]本发明提供一种MLCC用高性能离型膜及其制备方法,旨在解决现有刚性离型膜剥离超薄陶瓷生片时应力集中导致的生片破损问题,在不降低离型膜操作挺度、不影响离型力稳定性的前提下,大幅提升超薄陶瓷生片的剥离完整率

Benefits of technology

本发明所提供的MLCC用高性能离型膜摒弃了业内仅通过优化离型力和表面性能来改善剥离效果的固有思路,在刚性PET基材与离型层之间主动引入低模量弹性缓冲层;剥离过程中,缓冲层发生可逆弹性形变,增大剥离点弯曲曲率半径,使弯曲应力被有效分散和弛豫,从力学根源消除超薄陶瓷生片的应力破损。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898013A_ABST
    Figure CN122898013A_ABST
Patent Text Reader

Abstract

The application discloses a high-performance release film for MLCC and a preparation method thereof, and belongs to the technical field of film materials. The release film comprises a polyethylene terephthalate base material layer, and an elastic buffer layer and a silicone release layer are sequentially arranged on at least one surface of the base material layer. The elastic buffer layer is formed by a UV-curable composition, the glass transition temperature measured by a dynamic mechanical analyzer at a frequency of 1 Hz is -10 DEG C to 10 DEG C, the storage modulus at 25 DEG C is 20-100 MPa, and the thickness is 0.8-3.0 microns. According to the application, a specific low-modulus and room-temperature high-elasticity ultrathin elastic buffer layer is introduced between the rigid base material and the release layer. When the ultrathin ceramic green sheet is peeled, the buffer layer reversibly elastically deforms, the bending curvature radius of the peeling point is increased, the concentrated bending stress is effectively relaxed, the micro-cracks and fracture defects of the ultrathin green sheet are inhibited from the mechanical root, the green sheet integrity is improved under the premise that the peeling force is basically flat, and the operation stiffness and the peeling force stability of the release film are maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thin film materials technology, specifically relating to a high-performance release film for multilayer ceramic capacitor (MLCC) casting process and its preparation method, and particularly to a release film based on polyethylene terephthalate (PET). Background Technology

[0002] MLCCs are rapidly developing towards ultra-miniaturization and ultra-high capacity. The thickness of the ceramic dielectric layer has been reduced to 1.5 μm or even below 1.0 μm. The mechanical strength of ultra-thin ceramic green sheets is extremely low, and the peeling yield has become the core bottleneck restricting the mass production of high-end MLCCs.

[0003] Existing MLCC release films generally adopt a two-layer composite structure with a rigid PET substrate directly coated with an organosilicon release layer. There has long been a ingrained technical understanding and bias in this field: the rigidity of PET film is generally considered its core advantage as a release film substrate, providing stable support and precise handling for ceramic green sheets. Therefore, when problems arise with the peeling and breakage of ultra-thin ceramic green sheets, the improvement directions for those skilled in the art have always been limited to optimizing release agent formulations, smoothing the base film surface, antistatic modification, and heat resistance modification, aiming to further reduce release force or improve surface smoothness. Existing technologies have paid little attention to the problem of bending stress concentration at the peeling point of the rigid PET substrate, failing to recognize it as the root cause of ultra-thin green sheet breakage.

[0004] For example, Chinese patent CN114702714A discloses a high-adhesion silicone release agent that reduces release force through anchoring group modification; Chinese patent CN118163443A optimizes surface roughness by adding a nano-opening agent to the surface of the PET base film; Chinese patent CN117106220A introduces a POSS hard coating layer to improve the surface roughness and smoothness of the base film, and works in conjunction with a release layer anchoring system. Although the above-mentioned prior art improves certain properties of the release film in their respective directions, their improvement ideas have not deviated from the technical framework of "release agent / surface modification", and none of them involve improving the peeling mechanical environment; in actual production, even if the release force is reduced to 5... Below mN / cm, microcracks, pinholes, and fractures still frequently occur during the peeling of ultrathin green sheets. In-depth research revealed that the composite structure composed of rigid PET base film and hard release layer will form a sharp bend with an extremely small radius of curvature during peeling, forcing the ultrathin rigid ceramic green sheet attached to it to bear highly concentrated bending stress. This mechanical structural defect cannot be eliminated by reducing the release force or improving the surface smoothness.

[0005] Therefore, the industry urgently needs a release membrane structure that can eliminate bending stress concentration at the mechanical level and protect the integrity of ultrathin ceramic green sheets from the root. Summary of the Invention

[0006] This invention provides a high-performance release film for MLCCs and its preparation method, aiming to solve the problem of green sheet breakage caused by stress concentration when peeling ultrathin ceramic green sheets using existing rigid release films. Without reducing the operational stiffness of the release film or affecting the stability of the release force, it significantly improves the peeling integrity rate of ultrathin ceramic green sheets.

[0007] The present invention is achieved as follows: a high-performance release film for MLCCs includes a polyethylene terephthalate (PET) substrate layer with a thickness of 25–125 μm, and an elastic buffer layer and an organosilicon release layer are sequentially disposed on at least one surface of the PET substrate layer; the elastic buffer layer is formed of a UV-curable composition, and has a glass transition temperature of -10°C to 10°C measured by a dynamic mechanical analyzer at a frequency of 1 Hz, a storage modulus of 20–100 MPa at 25°C, and a thickness of 0.8–3.0 μm.

[0008] This invention introduces a specific low-modulus, room-temperature-temperature-high-elasticity, ultra-thin cross-linked elastic buffer layer between a rigid PET substrate and a hard release layer. During the peeling process, this elastic buffer layer can undergo reversible elastic deformation, cooperating with the overall bending of the PET substrate to significantly increase the bending radius of curvature (R) at the peeling point. This effectively disperses and relaxes the concentrated bending stress, effectively suppressing the stress breakage problem of ultra-thin ceramic green sheets from a mechanical perspective. At the same time, the buffer layer is extremely thin and cross-linked, completely preserving the overall operational stiffness and processing adaptability of the release film, and will not adversely affect the surface energy and release force of the release layer.

[0009] Preferably, the UV-curable composition forming the elastic buffer layer comprises, by weight: 30-60 parts of aliphatic polyurethane acrylate oligomer, 20-40 parts of monofunctional acrylate monomer, 5-15 parts of polyfunctional acrylate monomer, and 1-5 parts of photoinitiator; by the synergy of the aliphatic polyurethane acrylate with flexible segments and the mono / polyfunctional monomers that regulate the crosslinking density, the Tg and modulus of the cured film can be precisely controlled within the required range, achieving the optimal match of stress buffering function.

[0010] Preferably, the monofunctional acrylate monomer is selected from at least one of isobornyl acrylate and ethoxyethoxyethyl acrylate; the silicone release layer is preferably an addition-type solvent-free silicone release agent to ensure low release force, high residual adhesion and excellent stability, with a dry-basis coating weight of 0.08–0.2 g / m². 2 The thickness of the cured dry film is approximately 80–200 nm.

[0011] Preferably, the glass transition temperature of the elastic buffer layer is -5°C to 5°C, and the energy storage modulus is 30 to 60 MPa.

[0012] This invention also provides a method for preparing the above-mentioned high-performance release film for MLCCs, comprising the following steps: Step 1: Perform corona treatment on at least one surface of the polyethylene terephthalate substrate layer, said surface being the surface for which an elastic buffer layer is to be provided, in order to improve the surface dyne value; Step 2: Prepare the elastic buffer layer coating liquid and apply it to the surface of the corona-treated polyethylene terephthalate substrate layer. After pre-drying and UV curing, the elastic buffer layer is formed. Step 3: After activating the surface of the elastic buffer layer, apply an organosilicon release agent and heat to cure it to form an organosilicon release layer, thus obtaining the high-performance release film for MLCC.

[0013] Preferably, in step 2, the UV curing energy is 600–1000 mJ / cm². 2 The pre-drying temperature is 70-90℃ and the time is 20-40 s.

[0014] Preferably, in step 3, the heating and curing temperature is 120–140°C, and the curing time is 30–90 s; the activation treatment is a corona treatment with a treatment energy density of 0.5–2.0 kW·min / m³. 2 .

[0015] Compared with the prior art, the embodiments of this application have the following main advantages: The high-performance release film for MLCCs provided by this invention abandons the industry's conventional approach of improving the peeling effect solely by optimizing the release force and surface properties. Instead, it actively introduces a low-modulus elastic buffer layer between the rigid PET substrate and the release layer. During the peeling process, the buffer layer undergoes reversible elastic deformation, increasing the bending radius of the peeling point, effectively dispersing and relaxing the bending stress, and eliminating stress damage to the ultra-thin ceramic green sheet from the mechanical source.

[0016] The introduction of the elastic buffer layer does not change the surface interface characteristics of the release layer. The release force is determined by the release agent formulation itself, which remains stable and controllable. It significantly improves the integrity rate of the raw film without affecting the release force and operational stiffness. The buffer layer is extremely thin and cross-linked, and the overall film material has good stiffness, which is fully compatible with the operational precision requirements of automated casting and peeling production lines.

[0017] Simple structure, strong process compatibility, and easy mass production: It only requires adding a UV curing buffer layer coating process to the traditional release film production process. It is highly compatible with existing PET release film production lines, requires no modification to downstream equipment, and has high industrialization value. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the layer structure of the high-performance release film for MLCCs of the present invention.

[0019] Figure 2 This is a schematic diagram comparing the bending state of conventional release film and the release film of the present invention when peeling off ultrathin ceramic green sheets.

[0020] Figure label annotations: 1. PET substrate layer; 2. Elastic buffer layer; 3. Silicone release layer; 4. Ceramic green sheet; R, radius of curvature. Detailed Implementation

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein in the specification of the application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application; the terms "comprising" and "having," and any variations thereof, in the specification, claims, and foregoing drawings of this application are intended to cover non-exclusive inclusion. The terms "first," "second," etc., in the specification, claims, or foregoing drawings of this application are used to distinguish different objects, not to describe a particular order.

[0022] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0023] In this invention, the components of the elastic buffer layer coating liquid are not limited to 100 parts by weight; the relative proportions between the components determine the properties of the cured product. The elastic buffer layer coating liquid may also contain conventional additives such as leveling agents and defoamers to improve coating process performance and coating appearance.

[0024] Test Method Description Glass transition temperature (Tg) and energy storage modulus: Dynamic mechanical analyzer (DMA), tensile mode, frequency 1Hz, heating rate 3℃ / min, temperature scan range -50℃ to 100℃, Tg is taken as the temperature corresponding to the peak value of loss factor tanδ, and the energy storage modulus at 25℃ is taken as the elastic modulus.

[0025] Release force: According to FINAT 3 standard, TESA7475 standard tape is applied to the release surface, and a 2 kg standard pressure roller is used to roll it back and forth once. After being placed in an environment of 23±2℃ and 50±5%RH for 20 minutes, it is peeled off at a speed of 300 mm / min at 180°. The average value of the stable peeling section is taken.

[0026] Residual adhesion: The peeled TESA7475 tape was adhered to a standard stainless steel plate, and the peel force was measured under the same conditions. The percentage of the peel force was calculated compared to that of the original TESA7475 tape.

[0027] Ceramic green sheet integrity rate: A typical MLCC X7R ceramic slurry (barium titanate powder, polyvinyl butyral binder, dioctyl phthalate plasticizer, ethanol / toluene mixed solvent) was cast onto a release film and dried to obtain a ceramic green sheet of the target thickness. The green sheet was automatically peeled from the release film using a 180° peel tester at a speed of 300 mm / min. The surface of the peeled ceramic green sheet was observed under a 100x optical microscope, with 10 fields of view randomly selected (total observation area ≥ 10 mm²). 2 The percentage of the field of view area occupied by defects such as microcracks and pinholes is calculated by image analysis, and (1 - percentage of defect area) × 100% is used as the integrity rate of the raw film.

[0028] The activation treatment is a corona treatment with a treatment energy density of 0.5–2.0 kW·min / m³. 2 (equivalent to 30-120 kJ / m) 2 Preferably, after activation treatment, the dyne value of the elastic buffer layer surface is controlled at 38–44 mN / m.

[0029] Example 1 (1) Preparation of elastic buffer layer coating liquid Under light-protected conditions, 48 ​​parts by weight of aliphatic polyurethane diacrylate (Sartoma CN9001), 25 parts by weight of isobornyl acrylate (IBOA), 8 parts by weight of trimethylolpropane triacrylate (TMPTA), 3 parts by weight of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 0.5 parts by weight of leveling agent BYK-UV3500 are stirred and mixed evenly, and then degassed under vacuum for later use.

[0030] (2) Preparation of release film A 50 μm thick PET film was selected as the substrate layer, and its surface where the elastic buffer layer needs to be applied was subjected to corona treatment until the surface dyne value was ≥52 mN / m (tested according to GB / T 14216 standard). The above coating liquid was then applied to the treated surface using a microgravure coating method, dried with hot air at 80℃ for 30 s, and then cured with ultraviolet light at 800 mJ / cm². 2 The energy irradiation solidifies the material to form an elastic buffer layer with a thickness of 1.5 μm; according to DMA testing, the Tg of the buffer layer is -3℃, and the energy storage modulus at 25℃ is 38MPa.

[0031] The surface of the buffer layer was subjected to corona activation treatment with an energy density of 1.2 kW·min / m². 2(equivalent to 72kJ / m) 2 The dyne value of the elastic buffer layer surface after treatment is 42 mN / m.

[0032] The addition-type solventless silicone release agent (Dow Corning Syl-Off 7681 series, with vinyl silicone oil as the main agent and hydrogen-containing silicone oil as the crosslinking agent) and platinum catalyst were mixed uniformly using an online static mixer. The main agent and crosslinking agent were mixed according to the supplier's recommended ratio, and the platinum catalyst was added at 2% of the total weight of the main agent and crosslinking agent. After heating to 50°C to reduce viscosity, the mixture was applied to the surface of the activated elastic buffer layer using a microgravure coating method, with precise control of the wet coating amount. The dry coating amount was 0.12 g / m². 2 The film is heated and cured in an oven at 130°C for 60 seconds, and then rolled up to obtain the release film of the present invention.

[0033] Example 2 In Example 1, the monofunctional monomer was replaced with ethoxyethoxyethyl acrylate (EOEOEA), and the amount was adjusted to 40 parts. The amount of aliphatic polyurethane diacrylate was also 40 parts, and TMPTA was 5 parts, while other conditions remained unchanged. After curing, the thickness of the buffer layer was 2.5 μm, and the tested Tg was -5℃, with a storage modulus of 28 MPa. The release agent coating parameters were the same as in Example 1.

[0034] Example 3 The aliphatic polyurethane diacrylate in Example 1 was adjusted to 55 parts, IBOA 20 parts, TMPTA 8 parts, and photoinitiator 3 parts, with a cured thickness of 1.0 μm. The buffer layer Tg was 0℃, and the storage modulus was 65 MPa; the remaining conditions were the same as in Example 1.

[0035] Comparative Example 1 (Conventional release film without buffer layer) Using the same 50 μm PET film as in Example 1, after corona treatment, the same addition-type solvent-free silicone release agent (dry basis coating amount 0.12 g / m) was directly coated. 2 (Curing conditions: 130℃ / 60 s), without an elastic buffer layer.

[0036] Comparative Example 2 (Buffer layer parameters exceed the limits defined in this invention) The process of Example 1 was followed, but the elastic buffer layer formulation was adjusted to: 30 parts aliphatic polyurethane diacrylate, 30 parts IBOA, 25 parts TMPTA, and 3 parts photoinitiator. The cured film thickness was 1.5 μm, and the tested Tg was 25°C, with a storage modulus of 310 MPa (both Tg and modulus exceed the range of claim 1 of this invention); the rest was the same as in Example 1.

[0037] Performance test results Ceramic green sheets with a thickness of 1.2 μm were prepared using the release films of the above examples (for Example 2, a green sheet with a thickness of 1.0 μm was also prepared), and the tests were performed according to the aforementioned test methods. The results are shown in Table 1.

[0038] Table 1 Performance test results of each embodiment and comparative example As can be seen from Table 1: (1) The release films of Examples 1-3 of the present invention, when the release force is basically the same as that of conventional release films (Comparative Example 1), all achieve a peel integrity rate of 98.5% or higher for 1.2μm ultrathin ceramic green sheets, with the highest reaching 99.2%; Example 2 achieved an integrity rate of 98.8% in the test of 1.0μm ultrathin green sheets; while the integrity rates of Comparative Example 1 were only 81.5% and 78.2%; This shows that the introduction of the elastic buffer layer significantly reduces the peel damage of ultrathin green sheets without relying on reducing the release force.

[0039] (2) Although Comparative Example 2 also introduced an intermediate layer, its Tg (25°C) and storage modulus (310 MPa) both exceeded the range defined by the present invention, and its 1.2 μm green sheet integrity rate was only 85.3%, which is far lower than the 98.5% or more of the embodiment of the present invention. This comparative result shows that when the Tg and storage modulus of the intermediate layer are significantly higher than the above range, its stress buffering effect is significantly reduced. Controlling the Tg and storage modulus of the elastic buffer layer within the above range is beneficial to obtaining excellent stress buffering and green sheet protection effects. This parameter range is clearly critical.

[0040] (3) The residual adhesion rate of each embodiment remained above 94%, and the release force fluctuated little, indicating that the introduction of the elastic buffer layer and the corona activation treatment ensured the excellent adhesion and stable release performance of the release layer.

[0041] It should be noted that, for the sake of simplicity, the foregoing embodiments are all described as a series of actions. However, those skilled in the art should understand that the present invention is not limited to the described order of actions, as some steps may be performed in other orders or simultaneously according to the present invention. Furthermore, those skilled in the art should also understand that the embodiments described in the specification are preferred embodiments, and the actions and modules involved are not necessarily essential to the present invention.

[0042] It should be understood that the disclosed technical solutions in the embodiments provided in this application can be implemented in other ways. For example, the embodiments described above are merely illustrative, and the division of the units described above is only a logical functional division. In actual implementation, there may be other division methods. For example, multiple units or components may be combined or integrated into another system, or some features may be ignored or not executed. Furthermore, the coupling or communication connections shown or discussed may be indirect coupling or communication connections between devices or units through some interfaces, and may be in telecommunications or other forms.

[0043] The units described above as separate components may or may not be physically separate. The components shown as units may or may not be physical units; that is, they may be located in one place or distributed across multiple network units. Some or all of the units can be selected to achieve the purpose of this embodiment according to actual needs.

[0044] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on these embodiments, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still combine, add, delete, or otherwise adjust the features of the various embodiments of the present invention according to the circumstances without conflict or creative effort, thereby obtaining different technical solutions that do not fundamentally depart from the concept of the present invention. These technical solutions also fall within the scope of protection of the present invention.

Claims

1. A high-performance release film for MLCCs, comprising a polyethylene terephthalate substrate layer, characterized in that, An elastic buffer layer and an organosilicon release layer are sequentially disposed on at least one surface of the polyethylene terephthalate substrate layer; The elastic buffer layer is formed of a UV-curable composition, with a glass transition temperature of -10°C to 10°C measured at 1 Hz using a dynamic mechanical analyzer, a storage modulus of 20 to 100 MPa at 25°C, and a thickness of 0.8 to 3.0 μm. The elastic buffer layer can undergo reversible elastic deformation during the peeling process of ultrathin ceramic green sheets, increasing the bending radius of the peeling point and relaxing the concentrated bending stress, effectively suppressing microcracks and fracture defects generated during the peeling of ultrathin ceramic green sheets.

2. The high-performance release film for MLCCs as described in claim 1, characterized in that, The UV-curable composition comprises, by weight: 30-60 parts of aliphatic polyurethane acrylate oligomer, 20-40 parts of monofunctional acrylate monomer, 5-15 parts of polyfunctional acrylate monomer, and 1-5 parts of photoinitiator.

3. The high-performance release film for MLCCs as described in claim 2, characterized in that, The aliphatic polyurethane acrylate oligomer is an aliphatic polyurethane diacrylate.

4. The high-performance release film for MLCCs as described in claim 2, characterized in that, The monofunctional acrylate monomer is selected from at least one of isobornyl acrylate and ethoxyethoxyethyl acrylate.

5. The high-performance release film for MLCCs as described in claim 1, characterized in that, The glass transition temperature of the elastic buffer layer is -5℃ to 5℃, and the energy storage modulus is 30 to 60 MPa.

6. The high-performance release film for MLCCs as described in claim 1, characterized in that, The thickness of the polyethylene terephthalate substrate layer is 25–125 μm.

7. The high-performance release film for MLCCs as described in claim 1, characterized in that, The silicone release layer is formed by curing an addition-type solvent-free silicone release agent, with a coating amount of 0.08–0.2 g / m² on a dry basis. 2 .

8. A method for preparing a high-performance release film for MLCCs as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1: Perform corona treatment on at least one surface of the polyethylene terephthalate substrate layer, said surface being the surface for which an elastic buffer layer is to be provided, in order to improve the surface dyne value; Step 2: Prepare the elastic buffer layer coating liquid and apply it to the surface of the corona-treated polyethylene terephthalate substrate layer. After pre-drying and UV curing, the elastic buffer layer is formed. Step 3: After activating the surface of the elastic buffer layer, apply an organosilicon release agent and heat to cure it to form an organosilicon release layer, thus obtaining the high-performance release film for MLCC.

9. The method for preparing a high-performance release film for MLCCs as described in claim 8, characterized in that, In step 2, the UV curing energy is 600–1000 mJ / cm², the pre-drying temperature is 70–90℃, and the time is 20–40 s.

10. The method for preparing a high-performance release film for MLCCs as described in claim 8, characterized in that, In step 3, the heating and curing temperature is 120–140℃, and the curing time is 30–90 s; the activation treatment is a corona treatment with a treatment energy density of 0.5–2.0 kW·min / m³. 2 .

Citation Information

Patent Citations

  • Release film for MLCC and preparation method thereof

    CN114702714A

  • Online preparation method of low-roughness MLCC release film

    CN117106220A

  • MLCC release film and preparation method thereof

    CN118163443A